Architecture of Cocoa Genotypes in Colombia as Affected by Bud Type, Grafting Technique, and Pruning - Maria Denis Lozano Tovar; Jose Arboney Guzman; Luis Enrique Ramirez; Jairo Garcia (Indonesian Coffee and Cocoa Research Institute, 2022)
Organization of plant aerial parts and root distribution, environmental conditions such as light, temperature, humidity and agronomic practices (grafting and pruning) influences the final architecture of the plant. Most of cocoa plantations in Colombia belong to the plagiotropic type that emit branches and suckers in a disorderly way, which leads to an unbalanced development, this makes it difficult to manage. To search for cocoa plants with better architecture, we evaluated the effect of the type of the bud (orthotropic and plagiotropic), the grafting techniques (approximation and patch grafting) and pruning (structural and conventional) on ICS 95 and CCN 51 clones. The monitoring was carried out at an open greenhouse and field. Plants obtained from orthotropic buds and approximation grafting had lower bifurcation angles, 42% more leaves and 50% more branches. The structural pruning had a positive influence on the architectural variables, which presenteda higher conversion (8.68%) of fresh weight of cocoa pod into dry weight of cocoa beans, meanwhile CCN 51 trees showed a higher conversion (9.76%) compared to ICS 95 (7.34%). CCN 51 had the highest bean index (1.30) and the lowest pod index (22.0). This study demonstrated that structural pruning improved bean indexand pod index. We concluded that for CCN 51 by approximation grafting technique is a good alternative for a tropical dry forest, as its production between 1995 and 2277 kg of dry cocoa beans ha-1 year-1.